Association of HER-2/CEP17 Ratio and HER-2 Copy Number With pCR Rate in HER-2-Positive Breast Cancer After Dual-Target Neoadjuvant Therapy With Trastuzumab and Pertuzumab - Li, Fanfan; Ju, Qian; Gao, Cong; Li, Jingjing; Wang, Xiaolei; Yan, Min; Zhang, Liying; Huang, Meiling; Long, Qihe; Jin, Xiangting; Li, Nanlin (Frontiers in Oncology, 2022)
Objective To explore the correlation between HER-2 status and pathological complete response (pCR) in HER-2-positive breast cancer after dual anti-HER-2 neoadjuvant therapy with trastuzumab and pertuzumab. Methods A total of 57 HER-2-positive breast cancer patients admitted to the Second Affiliated Hospital of Anhui Medical University and Xijing Hospital Affiliated to Air Force Military Medical University, between January 1, 2019 and September 30, 2020, were enrolled in this multicenter retrospective study. HER-2 status, including HER-2/CEP17 ratio and HER-2/cell number ratio, was detected by FISH. The correlation between HER-2 status/clinicopathological data and pCR was analyzed. The ROC curve was drawn to determine the cutoff value. Results IHC assessment revealed 40 (70.18%) patients with IHC 3+ and 17 (29.82%) with IHC 2+. 41/57 (71.93%) patients achieved pCR. FISH revealed that the ratio of HER-2/chromosome 17 centromere (HER-2/CEP17) (p<0.001) and the ratio of HER-2/cell number (p<0.001) was significantly correlated with the pCR rate. ROC analysis showed that patients with an HER-2/CEP17 ratio ≥4.495 or HER-2/cell number ≥11.650 have a high pCR rate after dual anti-HER-2 neoadjuvant therapy, suggesting its predictive significance. Conclusion The response to dual-targeted neoadjuvant therapy with trastuzumab and pertuzumab was adequate in hormone receptor-negative, HER-2-positive breast cancer patients. HER-2/CEP17 ratio and HER-2/cell number ratio were crucial for predicting efficacy.